Linguistic Landscaping in India - (:unkn) unknown (My University, 2002)
Linguistic Landscaping serves not merely the communication of information function but also several other symbolic functions such as the assertion of ethno-linguistic identities, responses to language policies and discourse, and power structures embedded in language use.
Keywords: English